Efeitos de ciclos de umedecimento e secagem nos parâmetros de tensão de expansão e expansão livre de um solo expansivo - Oliveira, Larissa da Silva (2022)
Expansive soil is a typical example of unsaturated metastable, thin, predominantly clayey, and highly plastic soil. In its mineralogical composition, the notable presence of unstable argillominerals of the 2:1 type, such as montmorillonite and vermiculite, makes it susceptible to volume variations. Worldwide it is considered a problematic soil due to the damage that the effects of continuous swelling and shrinkage can cause to works built on it. When wet, this type of soil is able to present a high degree of expansion, which can be evaluated from the measurement of the swelling potential and the swelling pressure. When dry, however, expansive soil shrinks and can exhibit large volumetric variations. The swelling-shrinkage phenomenon of an expansive soil is therefore cyclical and directly dependent on a triggering element, especially the change in moisture. The climate, associated with the seasonal variations in temperature and moisture, acts as a favorable factor to trigger the manifestations of a potential expansive soil. Thus, arid and semi-arid regions are more susceptible to its occurrence. In situ, expansive soil goes through several wetting and drying cycles as a result of successive periods of rainfall and drought. The literature has indicated that seasonal variation in moisture can influence the change in certain geotechnical characteristics of expansive soils. In this context, with this study we propose to evaluate the effects that consecutive wetting and drying cycles can have on the swelling pressure and the swelling potential of an expansive soil specimen. To this end, geotechnical, chemical, mineralogical, and microstructural characterization tests of the specimen were performed. The soil expansiveness was quantified by swelling pressure tests - by the method of loading after expansion, with an overload of 0.5 kPa - and swelling potential, both in a cyclical manner, by performing eight continuous wetting and drying cycles. The results showed that the soil specimen tested consists of a inorganic high plasticity clay (CH), with high Atterberg limits and very high expansion potential. The chemical tests showed that the specimen corresponds to a young soil composed of primary minerals and silicate clays of the 2:1 type. Mineralogical analysis identified the presence of the argillominerals mica, smectite, montmorillonite and kaolinite, and microstructural observation found typical characteristics of argillominerals belonging to the mica and vermiculite groups. The evaluation of the swelling pressure and swelling potential based on the cyclic tests proved the influence of wetting and drying cycles on the swelling pressure and swelling potential of the soil. It was concluded that the highest values of swelling pressure and swelling potential are linked to the first cycle, and that the expansive behavior tends to decrease with the increase in the number of wetting and drying cycles.